PENGARUH DANA ALOKASI KHUSUS, PENDAPATAN ASLI DAERAH, DAN SISA LEBIH PEMBIAYAAN ANGGARAN TERHADAP BELANJA MODAL PEMERINTAH KABUPATEN/KOTA DI PULAU SUMATERA - Agil Novriansa; Ahmad Subeki (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2014)
The local government is expected to optimalize all its potential revenue for regional development in the form of capital expenditure. Some revenue sources of local government consist of special allocation funds (DAK), local own revenues (PAD), and remaining budget financing (SiLPA). This study aims to examine empirically the influence of DAK, PAD, and SiLPA on capital expenditure of district/city governments. This study used convenience sampling method based on the data availability. The sample of this study consistof 96 district/city governments in Sumatera with observation period in 2012. The result of multiple linear regression analysis shows that DAK, PAD, and SiLPA have positive effect on capital expenditure of district/city governments. This study expands the literature about the determinants of capital expenditure on local government.